Analysis of total phenolic content and antioxidant activity in Turi leaf extract (Sesbania grandiflora L.) with the use of different solvents - Amananti, Wilda; Perwita Sari , Meliyana (Journal of Natural Sciences and Mathematics Research, 2025)
This study aims to evaluate the effect of solvent types on the total phenolic content and antioxidant activity of turi leaf extract (Sesbania grandiflora). The types of solvents used include ethanol, ethyl acetate, and n-hexane. The total phenolic content was measured using the Folin-Ciocalteu method with gallic acid as a standard, while the antioxidant activity was determined using the DPPH quenching method. The results showed that the highest total phenol content was obtained from ethyl acetate solvent (12.31 µg/mL), followed by ethanol (9 µg/mL) and n-hexane (6.34 µg/mL). However, antioxidant activity based on IC50 showed different results, where the extract with n-hexane solvent had the highest antioxidant activity (IC50 = 142.9 µg/mL) compared to ethyl acetate (IC50 = 245.47 µg/mL) and ethanol (IC50 = 271.8 µg/mL). These differences indicate that the type of solvent affects not only the amount but also the type of phenolic compounds and other bioactive compounds in the extract. This study highlights the importance of selecting an appropriate solvent to enhance the extraction efficiency of phenolic compounds and antioxidant potential.